Theoretical and experimental characterization of Pr/Ce co-doped hydroxyapatites - Ibrahimzade, Lala; Kaygili, Omer; Dundar, Serkan; Ates, Tankut; Dorozhkin, Sergey V.; Bulut, Niyazi; Hssain, Ala Hamd (Elsevier, 2021)
This study presents a more extensive report on the experimental and theoretical characterization of the Ce-doped hydroxyapatite (HAp) samples additionally doped with Pr at varying amounts. To achieve this goal, four Ce-containing (a constant amount of 0.35 at.%) HAps additionally doped with Pr at various amounts (0.35, 0.70, 1.05, and 1.40 at.%) were synthesized via a combustion method. Besides, all these samples were modeled theoretically by using a density functional theory (DFT). Theoretical results showed that the bandgap energy decreased continuously from 4.5156 to 4.3097 eV. For all samples, the linear attenuation (or absorption) coefficient increased with the increasing amount of Pr and this parameter had a decreasing trend with the increase in the photon energy. An increase in the theoretical density and the lattice parameter c and a decrease of both the lattice parameter a and the unit cell volume were found. After analyzing the experimental data, the following results were observed: X-ray diffraction (XRD) and Fourier transform infrared (FTIR) data verified the formation of HAp phase (above 94% for all the samples) as the major phase and beta-tricalcium phosphate (beta-TCP) as the minor one. The amount of beta-TCP phase was found to increase from 3.4 to 5.9% with the addition of Pr. Similar to the theoretical findings, an increasing trend for the density and decreasing one for the unit cell volume were detected. Both a decrease in the crystallinity and an increase in the anisotropic energy density were found. The results of the thermal analysis supported the thermal stability of all the samples. The cell viability was found to be affected by Pr-content. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Powders: chemical preparation; Apatite; X-ray methods